Interwoven reinforced concrete structures: Integration of design and fabrication drivers through parametric design processes. (September 2017) - Erdine, Elif; Kallegias, Alexandros
Abstract : This paper addresses techniques directed towards the integration of form, structure, and composite material systems through a series of computational tools acting in correlation with digital fabrication processes for the realization of one-to-one scale, reinforced concrete architectural prototypes, designed and produced during the Architectural Association Summer DLAB Visiting Schools 2014 and 2016. The case studies investigate concrete and its inherent fluid materiality through generative form-finding methods, Finite Element Analysis, and various digital fabrication processes including robotic fabrication protocols. The paper highlights the integration of parametric design techniques with basic and advanced techniques of construction, moving away from conventional hierarchies prescribed by design, analysis, and fabrication as a linear model towards a unified model of design and production. Highlights: Integration of form, structure, and composite material systems are proposed. Strategies to construct interwoven concrete structures are described. The selected composite material system is reinforced concrete. Employment of fabric formwork and earth scaffolding is described. Employment of robotic rod-bending and Polypropylene formwork is described.